Ingresos y evasión tributaria de los comerciantes de la casona del mercado de Belén año 2022 - Zaina Gabriela, Valverde Novoa (2023)
The objective of the investigation was oriented to identify the characteristics of the income in a commercial conglomerate considering aspects such as the amount, control, registration, declaration and use of means of payment considering the high informality that occurs in the mansion of Belén de Igual In this way, tax evasion is addressed from the perspective of the merchant in the aspects of issuance and receipt of payment vouchers, amount of taxes, declaration, inspection, training and unreported income. For this purpose, a non-experimental descriptive investigation was carried out on 108 merchants, identifying that 73% of participants estimate income of up to S/ 10,000 per month, which present positive characteristics in an important group such as control of their income, tax awareness and the importance that income represents to cover costs and expenses, as well as negative characteristics in an important group such as the low use of means of payment, low accounting record, zero inspection and training actions, 52% present a high formal tax non-compliance and 29% present it medium, in relation to substantial tax non-compliance, 35% present a high level and 40% medium being a high data for the variable, the study concludes that the level of income is low for 73% and the level of tax evasion is high for 87%, estimating a percentage of undeclared income from 41% to 100%.